PELUANG DAN TANTANGAN PENERAPAN ASURANSI PERTANIAN DI INDONESIA: TINJAUAN KONSEPTUAL - Rohmah, Miftakhul (Jurnal Akuntansi AKUNESA, 2014)
Agricultural insurance is required as a risk management instrument for agriculture. The purpose this study is to analyze opportunities and challenges of agricultural insurance implementation in Indonesia. Implementation of agricultural insurance need some considerations, such: adopting agricultural insurance systems in several countries such as funding, operational and others, with some adjustments in accordance with the conditions in Indonesia then implementation of risk management for insurance companies and government regulations. Keywords: Agricultural Insurance, Opportunities, Challenges